Hubungan Laju Alir dan Viskositas Saliva dengan Tingkat Kecekatan Gigi Tiruan Penuh pada Pasien Rumah Sakit Gigi dan Mulut Universitas Andalas - Eni Rahmi; Sevty Agustin; Arymbi Pujiastuty (Faculty of Dentistry Universitas Andalas, 2019)
The most common complaint reported by patients in denture wearing is loose denture, caused by lack of retention. In the complete denture wearing, saliva plays an important role in retention. A well-fitting denture base to supporting tissues and the presence of adequate border seals will provide optimal denture retention. This condition can be achieved if it is supported by adequate volume, flow, and consistency of saliva. The purpose of this study is to determine the relationship between flow rate and viscosity of saliva with complete denture retention in Andalas Dental Collage and Hospital. This study used a cross sectional design. Thirty patients of complete denture wearers at the Andalas Dental Collage and Hospital were included in this study. Samples were selected through consecutive sampling method. Data were collected by using medical records, saliva viscosity assesstment, salivary flow rate measurement, and complete denture retention examination. Data were analyzed by Mann Whitney tes with p< 0,05. There was a significant relationship between salivary flow rate and maxillary complete denture retention (p= 0,002) and there was a significant relationship between saliva viscosity and maxillary complete denture retention (p= 0,002). However there was no relationship between salivary flow rate and mandibular complete denture retention (p= 0.101) and there was no relationship between saliva viscosity and mandibular complete denture retention (p= 0,223). The conclusion of this study was that the flow rate and viscosity of saliva was associated with maxillary complete denture retention yet was not associated with mandibular denture retention.